Lidocaine alleviates propofol related pain much better than metoprolol and nitroglycerin - Goktug,Asutay (2015)
ABSTRACTBACKGROUND AND OBJECTIVES: Injection pain after propofol administration is common and maydisturb patients' comfort. The aim of this study was to compare effectiveness of intravenous(iv) nitroglycerin, lidocaine and metoprolol applied through the veins on the dorsum of hand orantecubital vein on eliminating propofol injection pain.METHOD: There were 147 patients and they were grouped according to the analgesic adminis-tered. Metoprolol (n = 31, Group M), lidocaine (n = 32, Group L) and nitroglycerin (n = 29, GroupN) were applied through iv catheter at dorsum hand vein or antecubital vein. Pain was evalu-ated by 4 point scale (0 - no pain, 1 --- light pain, 2 --- mild pain, 3 --- severe pain) in 5, 10, 15and 20th seconds. ASA, BMI, patient demographics, education level and the effect of pathwaysfor injection and location of operations were analyzed for their effect on total pain score.RESULTS: There were no differences between the groups in terms of total pain score (p = 0.981).There were no differences in terms of total pain score depending on ASA, education level,location of operation. However, lidocaine was more effective when compared with metoprolol(p = 0.015) and nitroglycerin (p = 0.001) among groups. Although neither lidocaine nor metopro-lol had any difference on pain management when applied from antecubital or dorsal hand vein(p > 0.05), nitroglycerin injection from antecubital vein had demonstrated statistically lowerpain scores (p = 0.001).CONCLUSION: We found lidocaine to be the most effective analgesic in decreasing propofolrelated pain. We therefore suggest iv lidocaine for alleviating propofol related pain at operations.